2022
DOI: 10.3389/feduc.2022.1004286
|View full text |Cite
|
Sign up to set email alerts
|

Under the sword of Damocles: Exploring the well-being of university academics during a crisis

Abstract: Prompted by the wide-spread impact of the global pandemic on the higher education sector in Australia, this study explores the wellbeing and mental health of university academics who were caught in this altering landscape. This mixed-methods study has three objectives. Firstly, the study involved the design and development of an instrument to measure the wellbeing of university teachers. Secondly, the new instrument was administered to a randomly drawn sample of university academics, in order to validate its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…The COVID-19 pandemic exacerbated existing stressors among students enrolled in HEIs which further affected the HEI workforce 15,18–21 . Faculty and staff were impacted by lockdowns that required adjustment of their instructional activities, research efforts, and normal operations—in particular, rushing to migrate to online teaching without adequate preparation and support 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic exacerbated existing stressors among students enrolled in HEIs which further affected the HEI workforce 15,18–21 . Faculty and staff were impacted by lockdowns that required adjustment of their instructional activities, research efforts, and normal operations—in particular, rushing to migrate to online teaching without adequate preparation and support 22 .…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] The COVID-19 pandemic exacerbated existing stressors among students enrolled in HEIs which further affected the HEI workforce. 15,[18][19][20][21] Faculty and staff were impacted by lockdowns that required adjustment of their instructional activities, research efforts, and normal operations-in particular, rushing to migrate to online teaching without adequate preparation and support. 22 Saw et al examined COVID-19 pandemic stressors among university faculty and found that lack of readiness for online teaching had a significant impact on mental health, with a greater impact on female faculty.…”
Section: Stressors Specific To Higher Education Institutionsmentioning
confidence: 99%
“…Their activities are diverse and permeate teaching and research as well as administration. In addition to producing knowledge, they also engage in funding opportunities and other managerial services that lead them to play multiple roles: they are writers, teachers, collaborators, administrators, researchers, conveners, supervisors, leaders, entrepreneurs, negotiators, and advisors ( Subban et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A intensificação do trabalho e os mecanismos mercantis vigentes, iniciados a partir da implementação das políticas de ajuste neoliberais em meados dos anos 1990, levaram as universidades a uma atuação que segue as lógicas empresariais e a competitividade (Mancebo et al, 2006; Sindicato Nacional dos Docentes das Instituições de Ensino Superior [ANDES-SN,] 2013). Essas políticas provocaram mudanças significativas na atuação de seus trabalhadores, que atualmente acumulam em sua prática profissional os papeis de professores, colaboradores, administradores, pesquisadores, supervisores, líderes, empreendedores, negociadores e conselheiros (Subban et al, 2022).…”
Section: Apresentaçãounclassified